2022
DOI: 10.1002/hsr2.850
|View full text |Cite
|
Sign up to set email alerts
|

Short message service usage may improve the public's self‐health management: A community‐based randomized controlled study

Abstract: Background and Aims: The last decade has witnessed unprecedented growth in mobile phone use. It links millions of previously unconnected people. The ubiquity of mobile phones, which allows for use of the short message service (SMS), offers new and innovative opportunities for disease prevention and health education. SMS usage appears to be a feasible, popular, and effective way of improving health literacy. This study measured the effect of SMS health education on the improvement of health management in Shenzh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 40 publications
0
2
0
Order By: Relevance
“…Participants did suggest that being able to save or interact further with content on a personalized web location, for example, could further enhance the utility of the service, and this desire for increased integrated customizability was also shared by participants in the work of Shalaby et al [24,29]. The use of text messaging in the service of health education and promotion is emerging as opportunity to support improved health literacy, although some study has found challenges persist among those with the lowest literacy levels [42].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Participants did suggest that being able to save or interact further with content on a personalized web location, for example, could further enhance the utility of the service, and this desire for increased integrated customizability was also shared by participants in the work of Shalaby et al [24,29]. The use of text messaging in the service of health education and promotion is emerging as opportunity to support improved health literacy, although some study has found challenges persist among those with the lowest literacy levels [42].…”
Section: Discussionmentioning
confidence: 99%
“…The use of text messaging as a means to in uence health behaviour through both education and ongoing prompts or support is increasingly being explored [42,43]. In a community based RCT, Runsen et al [42] found that text messaging can surpass traditional health education information delivery methods such as pamphlets or other teaching methods. In this study, in the user interviews in particular, the effectiveness of SaskWell in creating awareness and use of new digital mental health tools was shared.…”
Section: Discussionmentioning
confidence: 99%